Report on JUICE 3GM gravity experiment performance - Cappuccio, P.; Benedetto, M. Di; Cascioli, Gael; Iess, L. (Copernicus, 2018)
The ESA’s JUICE mission will provide a multidisciplinary investigation of Jupiter and its Galilean moons through a suite of eleven different experiments. JUICE will perform 2 Europa flybys, more than 10 Callisto flybys, and will orbit about Ganymede in the last 9 months of the mission. The 3GM (Geodesy and Geophysics of Jupiter and the Galilean Moons) experiment will use accurate Doppler and range measurements to infer the moons' internal structure by measuring their gravity field and, for Ganymede and Callisto, their tidal Love number 𝑘₂ . This work presents the attainable 3GM gravity experiment performances with the latest trajectory kernels and the High Accuracy Accelerometer (HAA) to remove the dynamical noise induced by propellant sloshing.